Formalization of a novel Sugeno type adaptive fuzzy sliding mode controller for a class of nonlinear systems - Kucukdemiral, IB; Cansever, G (IEEE, 2005)
Formalization of a novel robust adaptive Sugeno based fuzzy sliding mode controller equipped with a supervisory controller is considered for the control of a class of nonlinear systems which significantly reduce computation via reducing the size of fuzzy rule base. Besides, all the system parameters such as control and state signals can be confined in a predefined bounded region by use of proposed control method. The proposed method does not need any information of the controlled plant and expertise.
Keywords: Sugeno type fuzzy control; sliding mode control; Computer Science; Engineering; Robotics